Competition Analysis of Small Industry in Pekanbaru, Riau - Triwijayanti, Wita; Iyan, Rita Yani; Zuriyani, Hilmah (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2024)
This study aims to analyze the business competition within the Crispy Mushroom industry in Pekanbaru City. The methodology employed in this study adopts a qualitative descriptive approach. The data utilized consists of both primary and secondary sources. Primary data is gathered directly from respondents through interviews, questionnaires, and documentation, while secondary data is obtained from government agencies such as the Central Bureau of Statistics for the City of Pekanbaru and the Department of Trade and Industry of the City of Pekanbaru. The analytical method applied is Porter's Five Forces Analysis, with the population and samples comprising 9 crispy mushroom businesses. The findings of the study reveal that competition within the small crispy mushroom industry in the city of Pekanbaru primarily revolves around promotional strategies. The competition in the crispy mushroom food business is characterized by verbal interactions between consumers and the utilization of social media platforms. To effectively navigate this competitive landscape and boost business sales, actors in the crispy mushroom industry need to strive for excellence in order to dominate the market. It is observed that utilizing promotions on social media yields greater effectiveness in increasing sales compared to solely relying on verbal communication with consumers.